Numerical Simulation for a Droplet Fission Process of Electrowetting on Dielectric Device (Communications in Computational Physics, 2010)
Electrowetting has been proposed as a technique for manipulating dropletssurrounded by air or oil. In this paper, we discuss the modeling and simulation of thedroplet fission process between two parallel plates inside an electrowetting on dielectric(EWOD) device. Since the gap between the plates is small, we use the two-phaseHele-Shaw flow as a model. While there are several high order methods around, suchas the immersed interface methods [1, 2], we decide to use two first-order methods forsimplicity. A ghost-fluid (GF) method is employed to solve the governing equationsand a local level set method is used to track the drop interface. For comparison purposes,the same set of two-phase Hele-Shaw equations are also solved directly usingthe immersed boundary (IB) method. Numerical results are consistent with experimentalobservations reported in the literature.